The Impact of Internal Variables on the Islamic Banks and Conventional Banks Financial Performance in Jordan: A Comparative Study - Abdo, Khawla K. (International Journal of Economics and Financial Issues, 2020)
The aim of this study is to explain the effect of the external variables on the financial performance of the Islamic and conventional banks measured by the rates of return of assets and the rates of return on equity, in addition to the earnings per stock during the period (2001-2011). To achieve the objectives of the study, some statistical procedures and E-views program are used. The data of the annual financial reports from the sample of the study are collected. The findings of the study indicated a statistical significant effect of the external variables on the performance of the conventional banks. According to Islamic banks, there was an effect of the external variables, on the financial performance. In addition, the findings showed that there were statistical significant differences in the rates of returns on assets between Islamic and conventional banks, but there were no significant statistical differences with respect to rates of return on equity, and the earnings per stock between the two kinds of banks. In light of these findings, the study has come up with some recommendations. The Islamic banks have to enhance their financial performance to be distinguished and to progress their activities. Keywords: conventional banks, Islamic Banks, External variables, financial performance JEL Classifications: G2, G21 DOI: https://doi.org/10.32479/ijefi.9521